Shape memory alloy (SMA)-cable-controlled sliding bearings: development, testing, and system behavior - Liang, Dong; Zheng, Yue; Fang, Cheng; Yam, Michael C H; Zhang, Chuntao (Smart materials and structures, 2020)
This paper presents an innovative type of friction sliding bearing system incorporating shape memory alloy (SMA) cables. The study commences with cyclic tests on individual SMA cables to understand their fundamental mechanical properties. The working principle of the proposed SMA-cable-controlled friction sliding bearing (SMA-sliding bearing) is subsequently described, followed by physical tests on two SMA-sliding bearing specimens. The bearing specimens show rectangular hysteresis loops induced by Coulomb friction before the SMA cables are stretched, and afterward the load resistance and energy dissipation capacity of the bearings are increased accompanied by certain self-centering capability due to the engagement of the SMA cables. Such action is expected to effectively restrict excessive displacements of the bearings and to help reduce the residual displacement. Following the experimental study, a theoretical model of the new bearing is developed and numerical simulation is carried out. The theoretical and numerical results agree very well with the experimental results. A case study focusing on a three-span continuous bridge subjected to pulse-like near-fault (NF) ground motions is subsequently conducted, where three types of bearing system, namely, conventional sliding bearing system, SMA-sliding bearing system, and steel-cable-controlled (steel-sliding) bearing system are compared. The system-level analysis results show that the proposed SMA-sliding bearing has its superiority in superstructure displacement control, with a limited increase in the curvature ductility of the pier.